THE IMPROVEMENT OF MADRASAH IBTIDAIYAH TEACHERS' COMPETENCE IN SEMARANG DISTRICT IN TERMS OF THE PERFORMANCE OF MADRASAH SUPERVISORS - Busaeri, Muhammad Agus; Winarno, Winarno (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
Teacher competence is one of the essential aspects of achieving educational goals and targets. The competence of teachers is also very influential in the learning process. The problem that often arises is that not all teachers have competencies by the standards set. This study aims to analyze the performance role of madrasah supervisors in improving the competence of Madrasah teachers and their obstacles. Qualitative research with a descriptive approach is the method used in this research. The informants of this study amounted to 12 people who were representatives of teachers, principals and madrasah supervisors in the Bringin sub-district, Semarang district, Central Java. Data collection used interview techniques and documentation with instruments in the form of structured interview guides and documentation checklist guides. Data analysis techniques used three steps: data reduction, presentation, and verification. The study results concluded that a good supervisor's role can affect a teacher's performance. The obstacles faced in supervision are the madrasah teachers experiencing a decline in performance due to age factors approaching retirement.